Edentulism And Factors Associated With Community Dwelling Elderly In Pasir Puteh, Kelantan, Malaysia - Azlan Jaafar; Mohd Zulkarnain Sinor; Norkhafizah Saddki; Ruhaya Hasan (Japan International Cultural Exchange Foundation, 2024)
Indexed by ERA